2020
DOI: 10.3390/antiox9030261
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Advanced Glycation End Products: Emerging Role of Iron in Androgen Deficiency in Obesity

Abstract: The literature suggests a bidirectional relationship between testosterone (T) and iron, but mechanisms underlying this relationship remain unclear. We investigated effects of iron on advanced glycation end products (AGEs) in obesity-related androgen deficiency. In total, 111 men were recruited, and iron biomarkers and N(ɛ)-(carboxymethyl)lysine (CML) were measured. In an animal study, rats were fed a 50% high-fat diet (HFD) with (0.25, 1, and 2 g ferric iron/kg diet) or without ferric citrate for 12 weeks. Obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In patients with β-thalassemia major, serum iron and especially non-transferrin-bound iron are typically elevated, and a positive correlation has been reported between this elevation and AGE (carboxymethyl-lysine and pentosidine) concentrations [97]. Correspondingly, in our recent experimental study Fe supplementation in obese rats induced a significant accumulation of AGEs and especially of CML in the liver [98]. Iron (Fe 3+ ) is capable of inducing formation of DNA-AGE adducts, especially when combined with glyoxal and arginine [99].…”
Section: Glycation and Age Toxicity In Ad As Influenced By Fesupporting
confidence: 60%
“…In patients with β-thalassemia major, serum iron and especially non-transferrin-bound iron are typically elevated, and a positive correlation has been reported between this elevation and AGE (carboxymethyl-lysine and pentosidine) concentrations [97]. Correspondingly, in our recent experimental study Fe supplementation in obese rats induced a significant accumulation of AGEs and especially of CML in the liver [98]. Iron (Fe 3+ ) is capable of inducing formation of DNA-AGE adducts, especially when combined with glyoxal and arginine [99].…”
Section: Glycation and Age Toxicity In Ad As Influenced By Fesupporting
confidence: 60%
“…ncoa4 is an autophagy cargo receptor, TFr1 is a transferrin receptor and dMT1 transports metal ions across membranes in mammals; all are necessary for iron release into the cytoplasm (34). The potential association between aGes level and iron overload has been suggested in previous studies (35,36). aGes were also reported to enhance heme oxygenase-1 (Ho-1) mrna expression in endothelial cells (37) and inhibited nrf2 activation in H9c2 cells (38).…”
Section: Discussionmentioning
confidence: 83%
“…This can lead to cell death, cell differentiation or reduced cell adhesion and migration. Previous studies have shown a potential association between AGEs levels and iron overload (Mirlohi et al, 2018;Chen et al, 2020). In patients with ß-Thalassemia major, iron overload and oxidative stress can increase the formation of AGEs and lead to different complications (Mirlohi et al, 2018).…”
Section: Agesmentioning
confidence: 99%